Sistem Informasi Siklus Pendapatan pada PT Prakasa Triputra Solusi - Eva Dwi Aprelia (PUTRA JAWA PUBLISHER, 2023)
The revenue cycle involves a series of business activities and related information processing that enables companies to provide goods or services to customers and collect cash as payment for these sales. Accounting Information Systems play a critical role in supporting the efficiency of transaction data processing within the revenue cycle. This research focuses on PT. Prakasa Triputra Solusi, with data retrieved through work practices, data recording, and documentation. The study concludes that the company's revenue cycle is performing well, and attributes this success to the competence of its employees in their respective fields. Overall, this research emphasizes the importance of effective accounting information systems in enabling efficient business operations within the revenue cycle.